PENINGKATAN KERJASAMA DAN TANGGUNG JAWAB DALAM MATERI IKLAN MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STAD PADA SISWA KELAS VC SD KANISIUS SENGKAN - INTANSARI DESY SAPUTRI; RISHE PURNAMA DEWI; DWI NATALI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This research aims to enhance cooperation and responsibility using the STAD learning model for fifth-grade students of Kanisius Sengkan Elementary School - Class V-C. This study is categorized as Classroom Action Research. The data collection techniques employed in this study encompass observation and questionnaires. The results of this study indicate that the STAD model can elevate cooperation and responsibility. This is substantiated by the increase in average cooperation questionnaire scores: from an initial condition of 50.83 to 64.82 in cycle I, and further to 77.05 in cycle II. Additionally, this enhancement is also evident from the increase in average observation scores for cooperation: from an initial condition of 38.48, to 56.06 in cycle I, and 70.30 in cycle II. The outcomes related to responsibility are reflected in the increased average questionnaire scores: from an initial condition of 54.77, to 60.62 in cycle I, and 78.3 in cycle II. Similarly, this is also seen in the augmented average observation scores, starting from pre-cycle at 41.91, to 59.59 in cycle I, and 70.70 in cycle II. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kerjasama dan tanggungjawab menggunakan model pembelajaran STAD pada siswa kelas V-C SD Kanisius Sengkan. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Teknik pengumpulan data yang digunakan dalam penelitian ini terdiri dari observasi dan kuesioner. Hasil penelitian ini menunjukkan bahwa model STAD dapat meningkatkan kerjasama dan tanggungjawab. Hal ini dibuktikan dengan adanya peningkatan rata-rata skor kuesioner kerjasama dari kondisi awal 50,83 siklus I 64,82, dan siklus II 77,05. Selain itu juga dilihat dari peningkatan rata-rata skor observasi dari kerjasama dari kondisi awal 38,48, siklus I 56,06 dan pada siklus II 70,30. Hasil tanggung jawab dapat dilihat dari peningkatan rata-rata skor kuesioner dari kondisi awal 54,77, siklus I 60,62, dan pada siklus II 78,3. Selain itu juga dilihat dari peningkatan rata-rata skor observasi dari pra siklus adalah 41,91, siklus I 59,59, dan siklus II 70,70.